1997
DOI: 10.1159/000111240
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Testosterone on Sexual Behavior, Reproductive Morphology and LH Secretion in the Female Rat

Abstract: Sexual differentiation of many brain structures and functions is dependent on levels of testosterone (T) or its metabolites during certain ''sensitive'' developmental periods. If T is present during these perinatal periods, masculinization and defeminization of sexual behavior occur; also, reproductive physiology, and central nervous system morphology and function are altered. The purpose of the present study was to characterize the influence of T at specific prenatal developmental intervals on offspring repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 17 publications
1
58
1
1
Order By: Relevance
“…Cultures from animals on P5, P7, P9 and P12 were investigated; the cultures from animals aged 4P15 did not stabilize satisfactorily. These ages were chosen to clearly separate the developmental stages of sexual differentiation known to occur during critical periods with often-abrupt limits 42 . Cultures were prepared using the roller tube method 43 .…”
Section: Methodsmentioning
confidence: 99%
“…Cultures from animals on P5, P7, P9 and P12 were investigated; the cultures from animals aged 4P15 did not stabilize satisfactorily. These ages were chosen to clearly separate the developmental stages of sexual differentiation known to occur during critical periods with often-abrupt limits 42 . Cultures were prepared using the roller tube method 43 .…”
Section: Methodsmentioning
confidence: 99%
“…From these results, since any endocrine disrupting activity of lindane is clearly weak, adverse effects might not have been expected in this study. A large number of investigations have shown effects of endocrine disruptors detected by examining AGD, nipple development, sexual maturation, estrous cycle, spermatogenesis, and sex organ weights (Aoyama and Suzuki, 2003;You et al, 2002;Ashby et al, 1997;Sharpe et al, 1995;Newbold et al, 1983;Yamasaki et al, 2005;Chamness et al, 1979;Clevenger et al, 1998;Gray et al, 1993Gray et al, , 1994Goldman et al, 1976;Rhees et al, 1997). Therefore, further studies using other chemicals, which have more definite endocrine disrupting activity, are considered necessary to establish the validity of the new protocol.…”
Section: Assessment Of the Test Methodsmentioning
confidence: 99%
“…Individuals are particularly sensitive to organizational effects of certain hormones during critical developmental periods. Whereas perinatal exposure to androgens is essential for masculinization of males, numerous studies have shown that females exposed to androgens during the appropriate perinatal period can be masculinized in morphology, physiology, and behavior (Huffman and Hendricks 1981;Rhees et al 1997;Thornton and Goy 1986;vom Saal 1979).…”
Section: Role Of Androgens In Reproductive and Behavioral Developmentmentioning
confidence: 99%